Pengaruh Gaya Kepemimpinan Kepala Sekolah terhadap Motivasi Kerja Guru SD Negeri Kecamatan Sekadau Hilir - Safitri Tuponawati; Luhur Wicaksono; Marinu Waruwu (Journal on Education, 2025)
This study investigates the influence of school principals' leadership styles on the work motivation of elementary school teachers in Sekadau Hilir District. Using a quantitative correlational design, data were collected through surveys distributed to all teachers in public elementary schools within the district. The findings reveal a weak but positive relationship between the principal's leadership style and teacher motivation. Transformational leadership styles exhibited a stronger impact compared to other styles, emphasizing the role of inspiration and support. Additionally, the influence of leadership was moderated by local work culture, suggesting that cultural factors significantly shape the effectiveness of leadership in fostering teacher motivation. These results underline the need for adaptive leadership that aligns with cultural dynamics to enhance teacher motivation and overall educational quality.